2021
DOI: 10.23865/hu.v11.2947
|View full text |Cite
|
Sign up to set email alerts
|

Rektorer i utbildning – drivkrafter för ett lärande i samspel

Abstract: Välutbildade skolledare ses som en viktig faktor i utveckling av den lokala skolan. År 2010 blev därför Rektorsprogrammet en obligatorisk utbildning på avancerad akademisk nivå. I en undersökning följer vi en grupp rektorer under de tre år de deltar i programmet. I denna artikel presenteras resultatet av en delstudie i den mer omfattande undersökningen om rektorer i utbildning. Under utbildningen är deltagarna organiserade i ”lärgrupper” i vilka de förväntas arbeta och lära tillsammans. Intentionen är också at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
(3 reference statements)
0
4
0
4
Order By: Relevance
“…However, it is important to note that when the principals were forced to deal with problems that occurred, they did not use their experiences from the training programme. One such example is how Jane described how she appreciated the trust that she and her colleagues felt while attending the training program, being indorsed to make choices concerning content and/or assignment based on what was essential for their learning group (for more information about the principal experiences and the program's design see Forssten Seiser & Söderström, 2021). Jane emphasised that this was a way of organising collegial learning in a way that strengthens both individual and collective understanding as it supports participants to be engaged in themes that are important to them in their professional practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to note that when the principals were forced to deal with problems that occurred, they did not use their experiences from the training programme. One such example is how Jane described how she appreciated the trust that she and her colleagues felt while attending the training program, being indorsed to make choices concerning content and/or assignment based on what was essential for their learning group (for more information about the principal experiences and the program's design see Forssten Seiser & Söderström, 2021). Jane emphasised that this was a way of organising collegial learning in a way that strengthens both individual and collective understanding as it supports participants to be engaged in themes that are important to them in their professional practice.…”
Section: Discussionmentioning
confidence: 99%
“…Leadership has received extensive attention as an essential ingredient in efforts to improve schools, with a growing consensus that improving the training of principals is worthwhile (Grissom et al, 2021). Studies on leadership training and its effects have identified a number of general principles that may underpin effective leadership training programmes (Clarke & Dempster, 2020;Darling-Hammond, LaPoint, & Meyerson, 2007;Dempster, Lovette, & Fluckinger, 2011;Hallinger, 2018;Huber, 2013;Leithwood & Steinbach, 1992;Pont, Nusche, & Moorman, 2008) A number of studies have illustrated the difficulty of combining theoretical and practical knowledge, emphasising the problem of connecting knowledge from educational practice with experience from leadership practice (Clarke & Dempster, 2020;Forssten Seiser & Söderström, 2021;Grootenboer & Hardy, 2015). A study of learning among principals in the Swedish National Principal Training Programme showed processes of continuous learning stretching between the training programme and the workplace (Jerdborg, 2021).…”
Section: Research Reviewmentioning
confidence: 99%
“…The course meetings are interspersed with literature reading and assignments addressing participants' practice (Forssten Seiser and Söderström, 2021;Norberg 2019;Brauckmann et al, 2020).…”
Section: Contextualizationmentioning
confidence: 99%
“…In the Swedish setting, Forssten Seiser and Söderström (2021) found that SNPTP participants develop diverse strategies according to their study group's culture. In some groups, a reflective learning community is formed, while in others effective collective routines are developed before examinations or an individualized culture is formed.…”
Section: Research On School Leaders' Professional Development In Educ...mentioning
confidence: 99%
“…I internationell forskning är pedagogiskt ledarskap inte ett etablerat begrepp på samma sätt som i svensk och nordisk forskning (Salo et al, 2015). Internationellt motsvaras pedagogiskt ledarskap gemensamt av begreppen transformational leadership (transformativt ledarskap) och instructional leadership (undervisningsorienterat ledarskap), även om en fullgod översättning inte är möjlig eftersom begreppet pedagogiskt ledarskap är socialt konstruerat och knutet till dess specifika kontext (Forssten Seiser, 2017;Ståhlkrantz, 2019). Transformativt ledarskap innefattar ledarens förmåga att stärka organisationens förbättringskapacitet genom att kommunicera en tydlig vision för det gemensamma uppdraget, främja det gemensamma lärandet och motivera medarbetarna (Leithwood & Jantzi, 2005).…”
Section: Rektors Pedagogiska Ledarskapunclassified